2020
DOI: 10.1111/jnu.12561
|View full text |Cite
|
Sign up to set email alerts
|

Hydration Choices, Sugary Beverages, and Kidney Injury in Agricultural Workers in California

Abstract: Purpose Agricultural workers working in high ambient temperatures are at risk for acute kidney injury. Despite recommendations to maintain hydration, workers likely do not drink enough to protect their renal function. Additionally, new research suggests that rehydration with sugary beverages adds additional risk to kidneys already stressed by high heat and workload. We assessed hydration choices during a work shift and tested associations of rehydration using sugary beverages with acute kidney injury. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…However, the association between recent consumption of soda among participants and lower eGFR disappeared after controlling for PSI. The lack of an association with soda consumption and eGFR is similar to the results reported by a recent study conducted in California among agricultural workers, in which there was no association between sugary drinks and AKI ( Moyce et al, 2020 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, the association between recent consumption of soda among participants and lower eGFR disappeared after controlling for PSI. The lack of an association with soda consumption and eGFR is similar to the results reported by a recent study conducted in California among agricultural workers, in which there was no association between sugary drinks and AKI ( Moyce et al, 2020 ).…”
Section: Discussionsupporting
confidence: 88%
“…Our results on water consumption and eGFR are consistent with other studies in which an increase on self-reported water consumption is associated with eGFR decline ( Laws, 2015 ; Sanoff et al, 2010 ; Wesseling et al, 2016 ). This supports the idea that perhaps the workers who drank large amounts may be compensating for working hard ( Moyce et al, 2020 ). It is important to consider the effect of hyperthermia alone or in combination with dehydration, as consequences of the strenuous physical work conducted during high levels of heat stress, which can lead to a reduced renal blood flow ( Cotter et al, 2014 ; Cuddy and Ruby, 2011 ).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…There are only three reports of the specific outcome of CKDnt in the United States (14)(15)(16). A few studies, although limited by the serum creatinine-defined criteria, have taken the important initial steps in quantifying postshift AKI incidence in US agricultural workers (18)(19)(20)(21)(22). In one study, agricultural workers in California experienced increased serum…”
Section: Discussionmentioning
confidence: 99%
“…Hotspots of end-stage renal disease of unknown causes have been identified in rural agricultural areas in the United States, including in the Mississippi river valley, southeast, California, and Texas (17). There are also a few preliminary reports of AKI in agricultural workers in California and Florida based on increased serum creatinine (18)(19)(20)(21)(22), and a recent retrospective analysis revealed that 40% of US military service members hospitalized with exertional heat stroke were diagnosed with AKI, but none required dialysis (11). To our knowledge, no study has investigated whether in situ occupational heat exposure increases markers of kidney injury among US workers.…”
Section: Introductionmentioning
confidence: 99%